Efficacy and Safety of Antibiotic Impregnated Microporous Nanohydroxyapatite Beads for Chronic Osteomyelitis Treatment: A Multicenter, Open-Label, Prospective Cohort Study - Chittawee Jiamton; Adinun Apivatgaroon; Saree Aunaramwat; Banchai Chawalitrujiwong; Chaiwat Chuaychoosakoon; Sitthiphong Suwannaphisit; Choen Jirawison; Chonlathan Iamsumang; Pinkawas Kongmalai; Pawaris Sukvanich; Pongtep Na Nakorn; Worawit Ongbumrungphan; et al. (MDPI AG, 2023)
Chronic osteomyelitis is still a serious health problem that causes disabling conditions and has an impact on the quality of life. The objective of this study was to determine the clinical efficacy and safety of localized antibiotics delivery via impregnated microporous nanohydroxyapatite (nHA-ATB) beads for chronic osteomyelitis treatment. A total of 62 patients were enrolled in this study. After radical surgical debridement, the bone defect was filled with three types of antibiotics (vancomycin or gentamicin or fosfomycin) impregnated HA beads. The follow-up period was 48 weeks. It was found that the success rate was approximately 98% with a re-infection in only one patient. Quality of life of all patients after treatment improved significantly over time. Systemic exposure to vancomycin and gentamicin after beads implantation was limited and high local antibiotics concentrations were found in wound drainage fluid at 24, 48 and 72 h. Blood biochemistry measurements did not show any nephrotoxic or hepatotoxic effects. 20 adverse events were reported, but 90% of the events were resolved without having to remove the beads and the patients recovered. Satisfactory outcomes were observed in terms of success rate, quality of life and adverse effect. nHA-ATB beads impregnated by vancomycin or gentamicin or fosfomycin could potentially be employed as an alternative product of choice for localized antibiotics delivery in chronic osteomyelitis treatment.